Decentralised Finance (DeFi) — How Tokenisation is Changing the Financial Industry - Volker Brühl (Wirtschaftsdienst)
Abstract Advances in distributed ledger technology are leading to a growing decentralisation of financial services (“decentralised finance”) that can be offered largely without intermediation by financial institutions. An important driver for this development is the ongoing tokenisation of assets, payments and rights, which enables the digital encryption of “crypto assets” on distributed ledgers. This article elaborates the foundations and fields of application of decentralised financial services with crypto assets that could challenge the established business models of financial institutions. This trend not only affects payment systems based on controversial crypto currencies such as Bitcoin, but also exchange platforms, capital markets solutions and corporate financing. A rapidly growing ecosystem of start-ups, tech companies and financial institutions is emerging, yet this ecosystem lacks a consistent regulatory framework. The European initiative MiCA (Markets in Crypto Assets) points in the right direction but needs to be adopted soon to ensure the future competitiveness of the European financial sector.